IMPACT OF ABIOTIC FACTORS ON POPULATION DYNAMICS OF INSECT PEST OF JATROPHA IN SOUTH GUJARAT - H. V. PATEL; K. G. PATEL; S. K. CHAWDA; M. R. SIDDHAPARA (The Bioscan, 2012)
Study was carried out to investigate population dynamics and impact of abiotic factor on population of insect pest complex of Jatropha (Jatropha curcas L.) under unprotected condition. The results of the field study revealed that the incidence of thrips (Retithrips syriacus Mayet) started from February with a peak during November (1.87 thrips/leaves) whereas it was nil during the month of July. The incidence of leaf miner (Acrocerops conflua Mayrick) was started from January with two peaks during months of May and November (0.65 and 0.55 leaf miner/leaf miner, respectively). The incidence of leaf webber (Salebria morosalis saalm Uller) was nil during the months of July with a peak during May (1.65 larvae/plant). The bugs (Scutellera nobilis Fabricious) were more active during the months of October to January with a peak of 0.14 bug/plant. Among various weather parameters, morning humidity and evening humidity were exhibited non-significant negatively relationship, while maximum temperature and sunshine hours showed positively non- significant influence on the population of the insect.